THE INFLUENCE OF LEADERSHIP STYLE, COMPENSATION POLICY, AND WORK DICIPLINE ON EMPLOYEE PERFORMANCE AT PT. JAPFA COMFEED INDONESIA, TBK HATCHERY WONOREJO - Evi Saskia Putri; Ikhsan Maksum (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of leadership style, compensation policy, and work discipline on employee performance at PT. Japfa Comfeed Indonesia, Tbk Hatchery Wonorejo. The research method used a quantitative approach with partial least square (PLS) data analysis to measure the relationship between variables. The results of the study show that leadership style has a positive and significant effect on employee performance, where an effective leadership style is able to increase employee motivation and productivity. A proper and fair compensation policy also has a significant influence on improving performance, as an adequate compensation policy encourages employees to work more optimally. In addition, work discipline has a significant positive influence on employee performance, where good discipline supports the achievement of the company's work targets. The research uses a sample technique in the form of saturated samples (census). The sample in this study was all employees of PT. Japfa Comfeed Indonesia, Tbk Hatchery Wonorejo as many as 160 people. Simultaneously, these three variables contribute significantly to improving the performance of PT. Japfa Comfeed Indonesia, Tbk Hatchery Wonorejo, so companies are advised to continue to optimize their leadership style, compensation policies, and work discipline to achieve optimal performance.